Assessment of non-vitamin k antagonist oral anticoagulant dosing patterns in Turkish patients with non-valvular atrial fibrillation a multicenter, cross-sectional study with insights from the aspect-noac study - Badak, Özer; Özkaramanlı Gür, Demet; Kaya, Çağlar; Önal, Tugay; Saydam, Onur; Aktürk, İbrahim Faruk; Aras, Dursun (My University, 2024)
Objective: We aimed to assess the real-world label adherence of non-vitamin K antagonis oral anticoagulant (NOAC) dosing patterns, including apixaban, edoxaban, and rivaroxaban, i Turkish patients with atrial fibrillation. Methods: This was an observational, prospective, cross-sectional, multicenter study. Patient with atrial fibrillation (AF) who were prescribed NOACs within the last 4 months were recruite from 34 cardiology clinics in Türkiye. Baseline data were initially collected, and patien awareness was evaluated at 3-4 weeks. Results: A total of 903 patients were enrolled in the study. The mean age was 72.84 ± 10.1 years. We found that 140 (15.5%), 721 (79.8%), and 42 patients (4.7%) were prescribe off-label low, on-label, and off-label high dosing, respectively. The age of the patients in th on-label group was significantly lower than that of those in the off-label low and off-label hig groups (both P < 0.001). Female patients were more frequently observed in the off-label hig group (P = 0.019). The body mass index values of the patients in the off-label high-dose grou were significantly lower than those in the other groups (P < 0.001). The perception of incom levels also revealed significant differences between the groups (P = 0.010). Furthermore, th HAS-BLED scores (the Hypertension, Abnormal Renal/Liver Function, Stroke, Bleeding Histor or Predisposition, Labile International Normalized Ratio, Elderly, Drugs/Alcohol Concomitantly were significantly lower in the on-label group than in the other groups (P < 0.001). Similarl the CHA2DS2-VASc [the Congestive Heart Failure, Hypertension, Age ≥75 (Doubled), Diabetes Stroke (Doubled), Vascular Disease, Age 65-74, and Sex Category (Female)] scores wer significantly lower in the on-label group than in the off-label group (P < 0.001). Conclusion: The clinical impact off-label NOAC prescriptions may vary. Therefore, raisin clinician awareness about proper NOAC dosing could aid in improve the outcomes.

Amaç: Atriyal fibrilasyonu (AF) olan Türk hastalarda apiksaban, edoksaban ve rivaroksaban dahil olmak üzere K vitamini antagonisti olmayan oral antikoagülan (NOAK) doz paternlerinin gerçek dünyadaki etiket uyumunu değerlendirmeyi amaçladık. Yöntem: Bu çalışma gözlemsel, prospektif, çok merkezli bir çalışmadır. Türkiye’deki 34 kardiyoloji kliniğinden son 4 ay içinde NOAK reçete edilen AF’li hastalar çalışmaya alındı. Başlangıç verileri başlangıçta toplandı ve hasta farkındalığı 3.-4. haftada değerlendirildi. Bulgular: Çalışmaya toplam 903 hasta dahil edildi. Yaş ortalaması 72,84 ± 10,17 idi. Çalışmada; 140 (%15,5), 721 (%79,8) ve 42 hastaya (%4,7) sırasıyla endikasyon dışı düşük, endikasyon dahilinde ve endikasyon dışı yüksek doz reçete edildiğini bulduk. Endikasyonu olan gruptaki hastaların yaşı, endikasyon dışı düşük ve endikasyon dışı yüksek gruptakilere göre anlamlı olarak daha düşüktü (her ikisi de P < 0,001). Kadın hastalar endikasyon dışı yüksek grupta daha sık gözlendi (P = 0,019). Endikasyon dışı düşük ve endikasyon dahilinde reçete edilen gruplardaki hastalar endikasyon dışı yüksek reçete edilen grupla karşılaştırıldığında anlamlı ölçüde daha obezdi (P < 0.001). Gelir düzeyi algısı da gruplar arasında anlamlı farklılıklar olduğunu ortaya koydu (P = 0,010). Ayrıca, HAS-BLED skorları endikasyon dahilinde reçetelenen grupta diğer gruplara göre anlamlı olarak daha düşüktü (P < 0,001). Benzer şekilde, CHA2DS2-VASc skorları etiket üstü grupta etiket dışı gruba göre anlamlı olarak daha düşüktü (P < 0,001). Sonuç: Endikasyon dışı NOAK reçetelerinin klinik etkisi değişiklik gösterir. Bu nedenle, uygun NOAK dozlaması hakkında klinisyen farkındalığının artırılması, sonuçların iyileştirilmesine yardımcı olabilir.
Kalp kapak hastalığı olmayan atriyal fibrilasyonlu Türk hastalarda vitamin k antagonisti olmayan oral antikoagülan (noac) dozlama paternlerinin değerlendirilmesi: aspect-noac çalışmasından görüşlerle çok merkezli, kesitsel bir çalışma
Keywords: Anticoagulants; Atrial Fibrillation; Dosing Pattern; Non-Vitamin K Antagonist Oral Anticoagulants; Patient Medication Knowledge; Antikoagülanlar; Atriyal Fibrilasyon; Dozlama Paterni; K Vitamini Antagonisti Olmayan Oral Antikoagülanlar; Hastanın İlaç Bilgisi